Novel method for dissolving copper-tin alloy

By combining ionic membrane technology with electrochemical technology, copper-tin alloys are dissolved by electrochemical method and composite additives are added to the electrolyte solution, the problems of low dissolution efficiency, large energy consumption and serious environmental pollution in the existing technology are solved, and an efficient, economical and environmentally friendly copper-tin alloy dissolution process is achieved.

CN119824430APending Publication Date: 2025-04-15YUNNAN RUNJIU TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510126063.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the recycling process of copper-tin alloys, the dissolution efficiency is low, the energy consumption is high, and the environmental pollution is severe, making it difficult to meet the needs of high efficiency, low cost and environmental protection.

Method used

By combining ion film technology with electrochemical technology, the electrolytic cell is separated into an anode chamber and a cathode chamber, the copper-tin alloy is dissolved by electrochemical method, and composite additives are added to the electrolyte to improve the stability of the dissolution process.

Benefits of technology

It realizes efficient dissolution of copper-tin alloy, with fast electrochemical dissolution rate and precise control, and the use of composite additives ensures the stability of the dissolution process. The process is simple and cost-effective, and is suitable for continuous production and large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824430A_ABST
    Figure CN119824430A_ABST
Patent Text Reader

Abstract

According to the novel method for dissolving the copper-tin alloy, the copper-tin alloy is dissolved into copper ions (Cu < 2 + >) and stannous ions (Sn < 2 + >) in an electrochemical mode, and the copper ions (Cu < 2 + >) and the stannous ions (Sn < 2 + >) are prevented from being separated out on a cathode again by means of the blocking effect of an ionic membrane. And meanwhile, a composite additive is added into the electrolyte, so that the stability of the dissolving process is enhanced. The method comprises the following steps: firstly, preparing an electrolyte containing inorganic acid and a composite additive, and separating an electrolytic bath through an ionic membrane; then, copper-tin alloy is arranged as an anode for electrolysis, the current density is 10 A / m < 2 >-5000 A / m < 2 >, and the temperature is 20-80 DEG C; and finally, the clear copper-tin solution is collected through filtering, and the anode scrap and the anode mud are recycled for reutilization. According to the method, the dissolution rate of the copper-tin alloy is effectively increased, the stability of the dissolution process is ensured, cyclic utilization and low-cost production are realized, and the method has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary resource recovery of nonferrous metals, and in particular relates to a new method for dissolving a copper-tin alloy. Background Art

[0002] As an important metal material, copper-tin alloy is widely used in the fields of electronics, electrical engineering, machinery and metallurgy. With the increasing demand for recycling electronic waste, waste cables and tinned copper wires, the recycling and reuse of copper-tin alloy has become a key technology in the field of resource recycling. Effective separation and recycling can not only reduce resource waste, but also increase the economic value of waste and promote sustainable development. At present, the recycling of copper-tin alloy mainly relies on physical and chemical methods. Due to the similar vapor pressure of copper and tin, physical methods (such as vacuum distillation) have low separation efficiency, high energy consumption and easy environmental pollution, which is difficult to meet the needs of efficient and low-cost recycling. The chemical method dissolves the copper-tin alloy into a salt solution and uses technical means such as selective precipitation, solvent extraction and electrolysis to achieve the separation and recovery of copper and tin. In the chemical method, dissolving the copper-tin alloy and preparing a mixed salt solution of copper and tin is the first step in the copper-tin separation and recovery process, and is also the basis of the entire recovery process. The key factors in the dissolution process of copper-tin alloy, such as the dissolution rate of copper and tin and their stability in the solution, directly affect the selection of subsequent separation technology and the optimization of operating conditions. Therefore, the efficient dissolution of copper-tin alloy becomes a key factor affecting the economy and environmental friendliness of the entire recycling process.

[0003] Since copper (Cu 2+ / Cu = 0.34V) and tin (Sn 2+ The standard electrode potential of copper-tin alloy (H⁺ / Sn = 0.14V) is higher than the standard electrode potential of hydrogen (H⁺ / H2 = 0V), so copper-tin alloy cannot be directly dissolved under acidic conditions. Existing copper-tin alloy dissolution methods mainly rely on high temperature, strong acid (such as sulfuric acid, nitric acid, etc.) and strong oxidizing environment to accelerate the dissolution process. Although these methods can achieve the dissolution of copper-tin alloy under certain conditions, they often face problems such as low dissolution efficiency, high energy consumption, and environmental pollution. Therefore, it is urgent to develop an efficient, economical and environmentally friendly copper-tin alloy dissolution method. Summary of the invention

[0004] The purpose of the present invention is to provide a new method for dissolving copper-tin alloy to solve the problems existing in the above-mentioned prior art.

[0005] The present invention combines ion membrane technology with electrochemical technology to dissolve copper-tin alloy. The electrolytic cell is separated into an anode chamber and a cathode chamber by an ion membrane. The copper-tin alloy dissolves in the anode chamber to generate copper ions (Cu 2+ ) and stannous ions (Sn 2+), due to the barrier of the ion membrane, they are prevented from migrating to the cathode chamber and precipitating again on the cathode. The cathode undergoes a hydrogen evolution reaction to generate hydrogen as a byproduct. At the same time, a composite additive is added to the electrolyte to enhance the stability of the dissolution process.

[0006] A new method for dissolving a copper-tin alloy comprises the following steps: (1) Prepare the electrolytic cell and prepare the electrolyte: The electrolytic cell is separated into an anode chamber and a cathode chamber by an ion membrane, and an electrolyte containing an inorganic acid and a composite additive is added into the two chambers.

[0007] (2) Electrochemical dissolution The copper-tin alloy was placed as the anode in the anode chamber, and the insoluble electrode material was placed as the cathode in the cathode chamber. A direct current was connected and the current density was set to 10A / m 2 ~5000A / m 2 , the electrolysis temperature is 20℃~80℃.

[0008] (3) Post-electrolysis treatment After the electrolysis is completed, the power is turned off and the residual anode is removed, the electrolyte is filtered to obtain a clarified copper-tin solution and anode mud, the copper-tin solution is collected, and the residual anode and anode mud are returned to smelting for the preparation of copper-tin alloy and electrochemical dissolution is performed again.

[0009] The ion membrane used in step (1) is an anion membrane or a proton membrane.

[0010] The inorganic acid used in step (1) is one of sulfuric acid, hydrochloric acid and nitric acid or a mixture thereof, and more preferably is sulfuric acid.

[0011] In step (1), the solution must be kept strongly acidic with a hydrogen ion concentration of 1.0 mol / L to 6.0 mol / L to prevent the formation of stannous ions (Sn 2+ ) undergoes hydrolysis during the dissolution process to generate tetravalent tin dioxide (SnO2) solid, which adheres to the metal surface and affects further dissolution.

[0012] The components of the composite additive used in step (1) are a complexing agent, a conductive enhancer and a surfactant. The composite additive can significantly improve the dissolution efficiency of the copper-tin alloy by optimizing the component ratio, enhance the stability of the electrolyte, and prevent the occurrence of side reactions. The total molar amount is 0.5 to 1.5 times the total molar amount of the copper and stannous ions finally obtained. The molar fractions of the complexing agent, the conductive enhancer and the surfactant are 40% to 80%, 10% to 30% and 10% to 30% respectively.

[0013] The complexing agent in the composite additive used in step (1) is a mixture of one or more of ethylenediaminetetraacetic acid (EDTA), sodium citrate (C6H5Na3O7), ammonium fluoride (NH4F) and tartaric acid (C4H6O6).

[0014] The conductive agent in the composite additive used in step (1) is a mixture of one or more sulfates such as potassium sulfate (K2SO4), sodium sulfate (Na2SO4) and ammonium sulfate ((NH4)2SO4).

[0015] The surfactant in the composite additive used in step (1) is a mixture of one or more of sodium dodecyl sulfate (SDS), sodium alkylbenzene sulfonate (LAS) and thiourea (CS(NH2)2).

[0016] In step (2), the mass fraction of copper in the copper-tin alloy is 1% to 99%, and the mass fraction of tin is 1% to 99%.

[0017] In step (2), the insoluble cathode is a titanium-plated precious metal coating or a non-precious metal coating electrode.

[0018] The present invention has the following technical effects: (1) The electrochemical method dissolves copper-tin alloy quickly and can be precisely controlled, thus improving production efficiency.

[0019] (2) The use of composite additives can effectively ensure the stability of the dissolution process.

[0020] (3) The process of the present invention is simple and low in cost, and can realize continuous production and large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited to the embodiments.

[0024] Example 1 A new method for dissolving copper-tin alloy: (1) Prepare the electrolytic cell and prepare the electrolyte: The electrolytic cell was separated into an anode chamber and a cathode chamber by an anion membrane, and 200 mL of electrolyte containing 1 mol / L sulfuric acid and 1.5 mol / L composite additives (ammonium sulfate, potassium sodium tartrate, and thiourea, with molar fractions of 10%, 50%, and 40%, respectively) was added to each chamber.

[0025] (2) Electrochemical dissolution 40g of copper-tin alloy (copper content 15%, tin content 85%, electrode size 5cm×5cm) was placed in the anode chamber as the anode, and titanium-plated iridium electrode material was placed in the cathode chamber as the cathode. Direct current was connected, and the current density was set to 500A / m 2 , the electrolysis temperature is 50°C. During electrolysis, the cell voltage is 0.85V.

[0026] (3) Post-electrolysis treatment After 12 hours of electrolysis, the power supply was turned off and the residual anode was taken out, with a mass of 9.6 g. The electrolyte was filtered to obtain a clarified copper-tin solution and anode mud. The concentration of stannous ions in the obtained electrolyte was 128.5 g / L, the concentration of copper ions was 10.0 g / L, and the mass of anode mud was 2.5 g. The residual anode and anode mud were returned to smelting to prepare copper-tin alloy and returned to the electrochemical dissolution step (2).

[0027] Example 2 A new method for dissolving copper-tin alloy: (1) Prepare the electrolytic cell and prepare the electrolyte: The electrolytic cell was separated into an anode chamber and a cathode chamber by an anion membrane, and 200 mL of electrolyte containing 1.5 mol / L sulfuric acid and 1.0 mol / L composite additives (ammonium sulfate, sodium citrate and sodium dodecyl sulfate, with molar fractions of 15%, 70% and 15%, respectively) was added to each chamber.

[0028] (2) Electrochemical dissolution 40g of copper-tin alloy (copper content 50%, tin content 50%, electrode size 5cm×5cm) was placed in the anode chamber as the anode, and titanium-plated iridium electrode material was placed in the cathode chamber as the cathode. Direct current was connected, and the current density was set to 1000A / m 2 The electrolysis temperature is 60 ℃ and the cell voltage is 1.25V during electrolysis.

[0029] (3) Post-electrolysis treatment After 6 hours of electrolysis, the power supply was turned off and the residual anode was taken out, with a mass of 11.2 g. The electrolyte was filtered to obtain a clarified copper-tin solution and anode mud. The concentration of stannous ions in the obtained electrolyte was 66.5 g / L and the concentration of copper ions was 61.0 g / L. The mass of the anode mud was 3.0 g. The residual anode and anode mud were returned to smelting to prepare copper-tin alloy and returned to the electrochemical dissolution step (2).

[0030] Example 3 A new method for dissolving copper-tin alloy: (1) Prepare the electrolytic cell and prepare the electrolyte: The electrolytic cell was separated into an anode chamber and a cathode chamber by an anion membrane, and 200 mL of electrolyte containing 1.0 mol / L sulfuric acid and 2.0 mol / L composite additives (ammonium sulfate, ammonium fluoride and sodium dodecyl sulfate, with molar fractions of 10%, 80% and 10%, respectively) was added to each chamber.

[0031] (2) Electrochemical dissolution 40g of copper-tin alloy (copper content 85%, tin content 15%, electrode size 5cm×5cm) was placed in the anode chamber as the anode, and titanium-plated iridium electrode material was placed in the cathode chamber as the cathode. Direct current was connected, and the current density was set to 800A / m 2 The electrolysis temperature is 60°C and the cell voltage is 1.05V during electrolysis.

[0032] (3) Post-electrolysis treatment After 10 hours of electrolysis, the power supply was turned off and the residual anode was taken out, with a mass of 8.3 g. The electrolyte was filtered to obtain a clarified copper-tin solution and anode mud. The concentration of stannous ions in the obtained electrolyte was 22.0 g / L and the concentration of copper ions was 120.0 g / L. The mass of the anode mud was 3.0 g. The residual anode and anode mud were returned to smelting to prepare copper-tin alloy and returned to the electrochemical dissolution step (2).

[0033] Comparative Example 1 No composite additives are added to the electrolyte: The electrolytic cell was separated into an anode chamber and a cathode chamber by an anion membrane, and 200 mL of sulfuric acid containing 1 mol / L (without composite additives) was added to each chamber. 40 g of copper-tin alloy (copper content 50%, tin content 50%, electrode size 5 cm×5 cm) was placed in the anode chamber as the anode, and titanium-plated iridium electrode material was placed in the cathode chamber as the cathode. Direct current was connected, the current density was set to 1000 A / m², the electrolysis temperature was maintained at 60°C, and the cell voltage was initially 1.25 V during the electrolysis process. After 1 hour of electrolysis, bubbles began to form on the anode surface, and the cell voltage increased sharply to 3.90 V. After continuing the electrolysis for 6 hours, the power supply was turned off and the residual anode was taken out, with a mass of 29.8 g. The electrolyte was filtered to obtain a clear copper-tin solution and anode mud. The concentration of stannous ions in the electrolyte was 23.5 g / L, the concentration of copper ions was 24.0 g / L, and the mass of anode mud was 0.6 g. The results show that the stability of the dissolution process is greatly reduced when composite additives are not added.

[0034] Comparative Example 2 Chemical dissolution of copper-tin alloy: Take 40g of copper-tin alloy (copper content 15%, tin content 85%), put it into a 1L beaker, add 150g / L sulfuric acid solution, and the liquid volume is 500mL. Control the temperature at 60°C, strongly supply oxygen at the bottom of the solution, and the oxygen flow rate is 20 L / h. After 5 days of reaction, the copper-tin alloy is completely dissolved to obtain a mixed salt solution containing copper ions (15g / L) and tin ions (85g / L). The dissolution rates are 1 / 10 of the rate in Example 1, 1 / 20 of Example 2, and 1 / 12 of Example 3, respectively. The results show that the chemical dissolution rate is significantly lower than the electrochemical dissolution rate.

[0035] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A new method for dissolving a copper-tin alloy, characterized in that: The following steps are involved: (1) Preparing an electrolytic cell and preparing an electrolyte: Using an ion membrane to separate the electrolytic cell into an anode chamber and a cathode chamber, and adding an electrolyte containing an inorganic acid and a composite additive into the two chambers; (2) Electrochemical dissolution: Place the copper-tin alloy as the anode in the anode chamber, and the insoluble electrode material as the cathode in the cathode chamber, connect direct current, set the current density to 10A / m² to 5000A / m², and the electrolysis temperature to 20℃ to 80℃; (3) Post-electrolysis treatment: After the electrolysis is completed, turn off the power supply and remove the residual anode, filter the electrolyte to obtain a clarified copper-tin solution and anode mud, collect the copper-tin solution, return the residual anode and anode mud to smelting, and use them to prepare copper-tin alloy, and then perform electrochemical dissolution again.

2. The method according to claim 1, characterized in that The ion membrane used in the step (1) is an anion membrane or a proton membrane.

3. The method according to claim 1, characterized in that: The inorganic acid used in step (1) is one or any combination of sulfuric acid, hydrochloric acid or nitric acid.

4. The method according to claim 1, characterized in that The hydrogen ion concentration of the electrolyte in step (1) is 1.0 mol / L to 6.0 mol / L.

5. The method according to claim 1, characterized in that The composite additive used in step (1) comprises a complexing agent, a conductive enhancer and a surfactant, and the concentration thereof is 0.5 to 1.5 times the total molar amount of the copper and stannous ions finally obtained. The molar fractions of the complexing agent, the conductive enhancer and the surfactant are 40% to 80%, 10% to 30% and 10% to 30% respectively.

6. The method according to claim 1, characterized in that The complexing agent in the composite additive used in step (1) is a mixture of one or more of ethylenediaminetetraacetic acid, sodium citrate, ammonium fluoride and tartaric acid.

7. The method according to claim 1, characterized in that The conductive agent in the composite additive used in step (1) is a mixture of one or more of potassium sulfate, sodium sulfate and ammonium sulfate.

8. The method according to claim 1, characterized in that The surfactant in the composite additive used in step (1) is a mixture of one or more of sodium dodecyl sulfate, sodium alkylbenzene sulfonate and thiourea.

9. The method according to claim 1, characterized in that: In the step (2), the copper mass fraction of the copper-tin alloy is 1% to 99%, and the tin mass fraction is 1% to 99%.

10. The method according to claim 1, characterized in that The insoluble cathode in step (2) is a titanium-plated precious metal coating or a non-precious metal coating electrode.